Faktor-Faktor yang Memengaruhi Keputusan Petani Cabai Merah di Indonesia untuk Mengambil Kredit - Silke Zorena Jono; Netti Tinaprilla; Feryanto Feryanto (University of Jember, 2022)
Red pepper is a horticulture commodity that has fluctuating prices in the market. The fluctuating price is affected by the availability of the peppers. Meanwhile, the availability of red peppers depends on production activities at the farm level. However, farmers require a big capital to produce these red peppers. Inadequate capital leads to low crop production, which is a common problem among these farmers. Farmer financing is done to overcome this low crop production, one of which is channelling credit to them. Although this credit facility has been provided, only a few farmers used it. Therefore, it is necessary to research the factors that influence Indonesian red pepper farmers’ decisions to use credit. This study uses a binary logistic regression model to determine factors that influence red pepper farmers’ decisions to use credit in Indonesia to use credit. The results revealed that farm location, age, formal education, gender, cooperative membership, farmers group membership, partnership, agricultural extension, and machinery significantly influenced the farmers’ decision to take credit as a capital resource.